Inheritance of Yield and Yield-related Traits in Highland Maize Hybrids of Uganda - Ninsiima Kayaga, Hellen; Kagoda, Frank; Ochwo-Ssemakula, Mildred; Mahulé Elysé Alladassi, Boris; Asea, Godfrey; Gibson, Paul; Edema, Richard (Journal of crop science and biotechnology, 2017)
Although many studies have been conducted on gene action of grain yield and yield related traits in maize, none of them focused on highland maize in Uganda. This study was conducted to establish the gene action controlling inheritance of yield and its related traits in highland maize hybrids. Thirty-six F1 hybrids generated from a 9 x 9 half diallel mating design, were planted with two local checks in three highland locations; Kalengyere, Kachwekano, and Buginyanya with two replications using a 2 x 19 alpha (0, 1) lattice design. Results showed that inheritance of ear length and anthesis-silking interval was controlled by both additive and non-additive gene action while the inheritance of days to anthesis, days to silking was mainly controlled by additive gene action. The inheritance of grain yield and other yield related traits was greatly influenced by environment and genotype x environment interaction. Considering the great influence of the environment and genotype x environment interaction on most of the traits including grain yield, further testing in additional locations over more seasons and broadening the genetic base of the parents is encouraged.
Keywords: Heritability; Highland; Hybrids; Gene action; Grain yield; Zea mays